The Educational Role of Majelis Ta'lim Al-Mubaroq in an Effort to Increase Community Worship in Cijati Village, Majalengka Regency - Rizqi Muhammad Firdaus Rizqi; Herdianto Wahyu Pratomo Herdi; Nuruddin Araniri Udin (International Journal of Educational Qualitative Quantitative Research, 2022)
This research focus include: 1) the educational role of Majelis Ta'lim Al-Mubaroq in an effort to increase community worship in Cijati village, Majalengka regency, 2) Implementation of community worship activities in Majelis Ta'lim Al-Mubaroq, Cijati village, Majalengka regency. The purpose of this study was to determine the process of the role of Majelis Ta'lim Al-Mubaroq in an effort to increase public worship in Cijati village and to determine the implementation of community worship activities as well as supporting and inhibiting factors of Majelis Ta'lim Al-Mubaroq in an effort to increase public worship in Cijati village, Majalengka regency. This study is a type of descriptive qualitative research using Islamic counseling guidance approach and sociological approach. Data collection using observation, interview and documentation methods, with data analysis techniques, namely data reduction, data presentation and conclusion. The results of this study indicate that the efforts made by majelis Ta'lim Al-Mubaroq in an effort to improve public worship in Cijati Village is to hold activities: routine recitation, tadarrusan, congregational prayers, carrying out activities such as community service, giving religious lectures and instilling religious understanding to the community against the values of Islamic teachings, all of which are very influential, while the, speaker/muballig and strong motivation from the manager and coach of Majelis Ta'lim. As for the inhibiting factors of the activities of the Majelis Ta'lim Al-Mubaroq, namely the lack of funds and lack of awareness of some members of the Majelis Ta'lim actively attending each activity. Implications of the study, expected to Majelis Ta'lim Al-Mubaroq in order to continue to increase its role in fostering and improving public worship and remain active and consistent in carrying out each activity. In addition, it is also expected to all competent parties such as coaches and teachers/muballig, in order to help foster members of the Majelis Ta'lim Al-Mubaroq.